Lifestyle, food consumption and body composition of university students - Rodrigo Nascimento de Lira, Carlos; Rufino da Silva, Lisanah; Barbosa Santos, Elane; da Conceição Pereira da Fonseca, Maria (O Mundo da Saúde, 2020)
Upon entering higher education, individuals experience changes that are reflected in their lifestyle. Therefore, the objective of this study was to know the lifestyle, body composition and food consumption of university students attended by the National Student Assistance Program. To this end, a cross-sectional study with 70 students was developed and questionnaires were applied to obtain information about lifestyle, level of physical activity, how they considered their food and a food frequency questionnaire to assess food consumption; weight and height were measured for the body mass index; waist circumference and a four skinfolds were measured for body fat percentage. Spearman's descriptive analysis and correlation was performed on IBM SPSS Statistics 21.0 to characterize, respectively, the sample and evaluate the relationship between the variables of income, their diet, nutritional status, physical activity, sex and area of study; food was assessed using food groups. The students considered themselves black and brown (80%), with a monthly income below one minimum wage (54.29%) and 45.71% were alcoholics. 67.14% were found to be eutrophic, 87.14% were not at risk for metabolic diseases, 47.14% had a body fat percentage above average and had a family history of chronic non-communicable diseases (77.14%). They demonstrated a varied diet, composed of all food groups resulting in a healthy diet profile. It is concluded that the students have a lifestyle that is not compatible with a healthy one, even though the food profile is closer to such a pattern.